The Effectiveness of Teaching Choice Theory to Parents with Psychiatric Disorders and Its Effect on their Children's Self-Concept and Self-Efficacy - Siahpoosh, Maryam (Shahroud Journal of Medical Sciences, 2025)
Background: Mental illness is the primary reason for disability among young individuals, making up a significant portion of the worldwide health issues experienced by teenagers, and can have lasting effects. This study aimed to determine the effectiveness of the theory of choice for parents with psychiatric disorders and its effect on their children's self-concept and self-efficacy.Methods: This research was a semi-experimental study using a pre-test-post-test design involving two experimental groups and one control group. The study population comprised all parents with psychiatric disorders who were diagnosed and were part of the Aheba Mental Illness Rehabilitation Center, totaling around 1000 in Tehran, Iran, 2024. Thirty parents with psychiatric disorders were randomly selected through a convenience sampling process and subsequently assigned to either an experimental group (n=15) or a control group (n=15). The experimental group participated in an eight-week structured choice theory, including reality therapy by Glaser, with one 90-minute session per week. The control group received no intervention. Data collection was facilitated using Symptom Checklist 90 (SCL-90R), The Self-Efficacy Scale (SES), and The Beck’s Self-Concept Test (BST). The inferential statistical method of multivariate analysis of variance was used for data analysis, with SPSS version 20 software being employed.Results: The findings suggest that the theory of choice training allows for a significant increase in self-efficacy and self-concept among children of parents with psychiatric disorders in the experimental group (Pvalue<0.05).Conclusions: Because the theory of choice training within a group supports internal control of people, the increasing internal control is causing increasing accountability, and therefore the increase in self-efficacy and self-concept. Therefore, group theory of choice training can be useful and applicable as a psychological therapeutic intervention for increasing self-efficacy as well as self-concept in children.